Mangrove Ecotourism Development Strategy: Identification of Supporting Factors, Barriers, and the Role of Stakeholders in Kubu Raya Regency - Mat Holik; Agus Sikwan; Indah Lystianingrum; Arkanudin Arkanudin; Ema Rahmania (International Journal of Business and Quality Research, 2025)
Teluk Berdiri Mangrove Ecotourism in Sungai Kupah Village, Sungai Kakap District, Kubu Raya Regency, is one of the environment-based tourist destinations that has the potential to improve the welfare of local communities. This study aims to identify the supporting and inhibiting factors of ecotourism development and the role of actors involved in its management. The research method used is a qualitative approach with observation techniques, in-depth interviews, and documentation studies. The results showed that the main supporting factors in the development of ecotourism include the uniqueness of natural attractions, government support in the form of infrastructure development and promotion, and active community involvement in tourism management. Several initiatives, such as the construction of bridges and roads to tourist areas and the holding of the Kubu Raya Traveler-Tourism Vlog Festival (KRTV Fest), helped increase the number of tourist visits, but there are various inhibiting factors in the development of this ecotourism, such as limited supporting infrastructure, lack of facilities such as lodging and clean water, lack of access to public transportation, and limited internet signals. In addition, limited promotion is still a challenge in attracting more tourists. The role of actors, including the government, local communities, academics and non-governmental organisations, is crucial in ensuring sustainable ecotourism management. This research confirms that synergy from various actors as well as infrastructure improvements and more effective promotional strategies are needed to optimise the potential of Telok Teluk Berdiri Mangrove Ecotourism as a sustainable community-based tourism destination.